STRUKTUR SEMANTIK VERBA PERSEPSI BAHASA MELAYU KUPANG: PERSPEKTIF METABAHASA SEMANTIK ALAMI (MSA) - Tualaka, Diaspora (Universitas Papua Manokwari, 2016)
East Nusa Tenggara is one of archipelago provinces consisting of various ethnics and languages. Kupang MalayÂ (KM) Â is a lingua franca used in daily communication. The use of KM lexicons especially in an inappropriate context can create misunderstanding among individual. To avoid this, it is important to comprehend the lexical meaning and how to use it properly. This short paper explains an approach of natural semantic meta-language in analyzing KM data especially perception Verb SEE by using descriptive analysis method and applying natural semantic meta-language Â theory proposed by Weirzbicka (1996).In natural meaning viewpoint proposed by Weirzbicka, perception Verbs in Kupang Malay are formed by mental predicate SEE. This paper focuses only on describing semantic features of every lexicon Â which has meanings derived from verb SEE. NMS uses semantic analysis approach which is based on the formation of the paraphrase. Semantic Structure of Perception Verb in KM is formed by mental predicate consisting of natural meaning expalined as follows: Â âsomeone saw somethingâ in Kupang Malay liat âseeâ is realized with âmaloiâ, âmalerokâ, âlotiâ, âpareksaâ, âbasukâ. Based on the results of analysis, it is concluded that the semantic structure of Perception verb Kupang Malay has 3 types, sub-types and even sub-sub-type that describe the meaning configuration of each lexicon. Distinguishing features can be seen in the mapping and explication.Â